The dissemination of brain imaging guidelines and recommendations - Andy Wai Kan Yeung; Pradeep Singh; Simon B. Eickhoff (IBRO Neuroscience Reports, 2022)
Many neuroimaging guidelines and recommendations have been published in the literature to guide fellow researchers to conduct and report research findings in a standardized manner. It was largely unknown if they were cited or read by the scientific community. Analyses were conducted to assess their impact in terms of citations, Twitter posts, and Mendeley reads. Web of Science Core Collection database was accessed to identify relevant publications. The number of their Twitter posts and Mendeley reads were recorded from Altmetric and Mendeley databases respectively. Spearman correlation tests were conducted to evaluate if the citation count had a relationship with these metrics. When all 1786 publications were considered, citation count had a strong positive correlation with Mendeley reads (rho = 0.602, p < 0.001), but a weak negative correlation with Twitter posts (rho = −0.085, p < 0.001). When publications in the 2010 s were specifically considered, citation count had an even stronger positive correlation with Mendeley reads (rho = 0.712, P < 0.001), whereas the correlation with Twitter posts became positive but still weak (rho = 0.072, P = 0.012). Temporal profiles of citation and Mendeley counts showed that these guidelines and recommendations had a relatively stable influence in the field for years after being published.